Improving Prospective Basic Education Teachers' Capabilities on Digital Literacy: A Systematic Literature Review - Uswatun Hasanah; Sri Rahayu; Ade Ika Anggraini (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractDigital literacy is a fundamental competency that must be mastered in the 21st century. Digital literacy skills are the key to presenting interesting, interactive, actual, and factual learning. Therefore, efforts to improve the digital literacy abilities of prospective teachers need to be carried out. The purpose of this research is to explore the efforts that need to be made by teachers and institutions to improve teachers' digital literacy skills. The method used in this research is a literature study. Literature is obtained from various kinds of research articles that are reputable in the national and international spheres. Article analysis was carried out by examining efforts to increase digital literacy skills from each source, and categorizing several efforts into several categories. The results of this study indicate that there are several efforts to improve the digital literacy abilities of prospective teachers, including, procuring partnership programs between tertiary institutions and schools, developing digital-based teaching modules, developing digital web in the learning process, increasing digital literacy skills of prospective teachers using product-based methods, such as making videos/learning media), using problem-solving-based methods, using some frameworks in implementing education, procuring supporting facilities and developing curricula that integrate digital literacy content into each subject.Keywords: digital literacy, prospective teacher, basic education.Â AbstrakLiterasi digital merupakan kompetensi dasar yang harus dikuasai di abad 21. Kemampuan literasi digital menjadi kunci tersajinya pembelajaran yang menarik, interaktif, aktual, dan faktual. Oleh karenanya, upaya peningkatan kemampuan literasi digital calon guru perlu dilakukan. Tujuan dari penelitian ini adalah untuk mengeksplorasi upaya-upaya yang perlu dilakukan oleh guru maupun lembaga untuk meningkatkan kemampuan literasi digital guru. Metode yang digunakan dalam penelitian ini adalah studi literatur. Literatur didapatkan dari berbagai macam artikel penelitian yang bereputasi dalam ranah nasional dan internasional. Analisis artikel dilakukan dengan menelaah upaya-upaya peningkatan kemampuan literasi digital dari setiap sumber, dan mengkategorikan beberapa upaya menjadi beberapa kategori. Hasil penelitian ini menunjukkan terdapat sejumlah upaya dalam meningkatkan kemampuan literasi digital calon guru, diantaranya, pengadaan program kemitraan antar perguruan tinggi dan sekolah, pengembangan modul ajar berbasis digital, pengembangan web digital dalam prose pembelajaran, meningkatkan kemampuan literasi digital calon guru dengan menggunakan metode perbasis produk (seperti membuat video/media pembelajaran), menggunakan metode berbasis pemecahan masalah, penggunaan sejumlah frame work dalam pelaksanaan pendidikan, pengadaan fasilitas yang mendukung dan mengembangkan kurikulum yang mengitegrasikan konten literasi digital ke dalam setiap mata pelajaran.Kata kunci: literasi digital, calon guru, pendidikan dasar.